Enhancing Access to Justice for Street Children through a Rights-Based Perspective on Sustainable Development Goals - Sandy Kurnia Christmas; Anisyaputri Anisyaputri; Jean Claude Geofrey Mahoro (Universitas Internasional Batam, 2023)
Street children represent a consequence of the urban divide, reflecting a disparity within urban areas. These children live in precarious conditions with limited opportunities for a respectable life. This study aims to explore the Government's involvement, particularly in terms of policy preparedness and infrastructure, aimed at improving the quality of life for street children and ensuring their fair access to justice. This research endeavor intends to analyze procedural policies and governmental initiatives directed at realizing sustainable development goals pertaining to the rights of street children. The findings of this investigation reveal that the government is actively engaged in endeavors to grant street children their rights and to actualize sustainable development objectives. Notably, various existing measures encompass the establishment of interim shelters, serving as educational facilities and platforms for the fulfillment of other rights for these children. However, there remains room for enhancement in these efforts, necessitating a broader reach to encompass regions with substantial populations of street children. This expansion is imperative to effectively achieve sustainable development goals through the comprehensive fulfillment of the rights of street children.